Analisa Faktor Internal dan Manajemen Resiko PT ESP dalam Memanfaatkan Tandan Kosong Kelapa Sawit sebagai Alternatif Bahan Bakar Terbarukan - Indah Nur Lestari; Edi Hamdi; Muhammad Dhafi Iskandar; Dimas Angga Negoro (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to identify the risk management process along with risk sources, assess the risks that may arise and analyze the strategies that will be carried out in the planning of Utilizing Empty Palm Oil Fruit Bunches as an Alternative Renewable Fuel to handle or manage risks that may occur. The method used in this activity is to collect data, observe, analyze and evaluate the results of this activity to be able to predict the possibility and impact of risks that occur during the business so that it can be used as a guideline in determining the next steps to evaluate obstacles and threats that are grouped according to their scale. This study explores the technical and economic feasibility of utilizing EFB waste from the palm oil industry for energy production. The use of EFB pellets has proven to be more cost efficient and provides significant environmental benefits, including reducing greenhouse gas emissions compared to the use of conventional coal. In addition, this project supports Indonesia's renewable energy targets and encourages sustainable waste management practices in the palm oil sector. This study also raises the potential for implementing circular economy principles by converting industrial waste into valuable energy sources. Recommendations include optimizing the supply chain and developing pellet production technology to increase efficiency and ensure the long-term sustainability of this project.